PELATIHAN PENGEMBANGAN JASA PENJAHIT TAILOR PENGABDIAN MAHASISWA INDO GLOBAL MANDIRI - Adelia Prameswari, Femy; Hertati, Lesi; Terttiaavini; Heryati, Agustina; Asmawati (Transpublika Publisher, 2021)
The development of technology and information systems has significantly impacted the sewing machine and textile industries, thereby influencing the tailoring profession. Clothing has become an essential human requirement. Juki Tailor, a tailor shop that has been operational since 1965, specializes in sewing services for official attire, including PDU/PDH TNI-POLRI uniforms, civil servant uniforms, clothing alterations, pants adjustments, and various other garment types. Currently, Juki Tailor utilizes a combination of manual systems, such as in-person product sales and offline promotional methods like word of mouth, as well as online channels like WhatsApp. This research aims to investigate the relationship between the potential of the tailor business and income generation. An individual's financial status can be measured through the concept of income, which represents the total amount of money received within a specific time frame.